Justiça diferenciada para a superação de uma vida precária - Antônio Eduardo Silva Nicácio (2011)
In this dissertation, three elements for the establishment and systematic reproduction of a precarious life recurrent in Brazilian society will be identified. They are: a) symbolic violence, which is reviewed through the concealment of the abandonment and the denial of recognition of certain subjects and minority social groups, as well as through the predominance of domination, discrimination and subordination relations; b) culture of poverty, characterized by the constant presence of dysfunctional families, with precarious habitus and wounded integrity - both individually and collectively - that are marked by the generalization of low self-esteem, lack of confidence and violation of autonomy. Such situations are exacerbated by the romanticized theoretical readings of the oppressed people; c) naturalization of inequality, due to the effects of the Brazilian modernization process and the prevalence in our society of a meritocratic and economicist logic supported by a social, political and legal consent. From the theoretical analysis of the precarious life contexts, the paper will lean on a proposal for a theory of a Differentiated Justice, based on recognition, respect and appreciation of different normative dimensions of human life, namely, ethical, moral, political and legal. It is believed that such a theory may have the capacity to promote the social inclusion and self-realization of individuals and social groups, understood in a multidimensional and emancipated manner. Such a theory will have as distinctive attribute the following commitments: to work for the development of a sense of belonging extended to a moral community and of involvement and solidarity to the ethical and political communities; to recognize the particular differences of the minority social groups and create conditions for the construction and satisfaction of the social and ethical esteem; to develop the sense of political and legal responsibility and create conditions for genuine participation, effective, critique and extensive; and, finally, to achieve the principles of radical democracy, factual freedom and legal equality, through measures of genuine participation, effective representation and social equalization.